Impact of Completion of a Pre-Pharmacy Biochemistry Course and Competency Levels in Pre-Pharmacy Courses on Pharmacy Student Performance - Ruth Vinall; Parto Khansari; Jason McDowell; L. Douglas Ried; Eugene Kreys (MDPI AG, 2019)
Poor performance in foundational science courses, which are usually taken during the first or second year of pharmacy school, can have several negative consequences including increases in student drop-out rates and increases in the number of dismissals and remediating students. The primary goal of the current study was to determine whether completion of a pre-pharmacy biochemistry course and/or performance on a biochemistry competency test (administered at the beginning of the pharmacy program) are associated with pharmacy student performance in foundational science courses and overall academic performance. A secondary goal was to determine whether performance in pre-pharmacy courses and/or student demographics are associated with pharmacy student performance. Prospective univariate analyses (n = 75) determined that completion of a pre-pharmacy biochemistry course is not associated with pharmacy student performance. However, performance on a biochemistry competency test was associated with performance in Biochemistry and Cell&Molecular Biology (p = 0.002). Furthermore, post-hoc analyses determined that pre-pharmacy cumulative chemistry GPA correlates with performance in both the Biochemistry and Cell&Molecular Biology and Medicinal Chemistry foundational science courses (p = 0.002 and p = 0.04, respectively) and can predict first year GPA (p = 0.002). The combined data indicate that further assessment of the impact of pre-pharmacy competency in biochemistry and chemistry on pharmacy student success is warranted.